1997
DOI: 10.1002/hep.510260612
|View full text |Cite
|
Sign up to set email alerts
|

Human hepatic myofibroblasts increase invasiveness of hepatocellular carcinoma cells: Evidence for a role of hepatocyte growth factor

Abstract: RT-PCR and Western blot analysis confirmed thatAlso, tumor-associated MF have been shown to be involved both tumor cell lines expressed c-met, the receptor for HGF.in the in vivo and in vitro invasiveness of colon cancer cell The effects of MF-conditioned medium were not reproduced lines. 6 by acidic fibroblast growth factor, basic fibroblast growth Hepatocyte growth factor (HGF) is a multifunctional cytofactor, epidermal growth factor (EGF), transforming growth kine that has been implicated in the pathogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(48 citation statements)
references
References 2 publications
3
45
0
Order By: Relevance
“…It was observed that iHSC-CM promoted the proliferation, migration and invasion of HCC cells in vitro , a result consistent with previous studies (9,15,16). Our in vivo results were similar.…”
Section: Discussionsupporting
confidence: 91%
“…It was observed that iHSC-CM promoted the proliferation, migration and invasion of HCC cells in vitro , a result consistent with previous studies (9,15,16). Our in vivo results were similar.…”
Section: Discussionsupporting
confidence: 91%
“…HepG2 cells are hepatocellular tumor cells that express c-Met 32 and respond to exogenous HGF by exhibiting elevated cell motility and matrigel invasion, 33,34 which coincides with suppression of cell proliferation 33 and formation of tubular to completely block ligand binding and showed subnanomolar potencies ( Fig. 1A; Table 1) that correlated well with the binding activity observed in the ECD binding ELISA and affinity measurements using Biacore ( Table 1).…”
Section: ##supporting
confidence: 64%
“…HGF, which is predominantly expressed in HSC and endothelial cells in the normal liver, has been detected in cirrhotic liver tissue, adenomas, and 80% of HCC cases (159). Neutralization of HSC-secreted HGF inhibits the proliferation and invasion capacity of HepG2, Huh7, Hep3b, and PLC cells in vitro (83, 160). Tumor promotion by HGF is attributed to MAPK/ERK-induced proliferation and survival signals in HCC (reviewed in 161) and activation of a c-Met/FRA1/HEY1 signaling cascade that contributes to HCC invasiveness and chemoresistance (81).…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%